2008
DOI: 10.1242/jeb.007187
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypy, flexibility and coordination: key concepts in behavioral functional morphology

Abstract: SummaryAnimal movement and its muscular control are central topics in functional morphology. As experimentalists we often manipulate stimuli in a controlled setting or compare species to observe the degree of variation in movement and motor control of particular behaviors. Understanding and communicating the biological significance of these sources of variability requires a universal terminology that is presently lacking in the functional morphology literature. We suggest that ʻstereotypyʼ be used to refer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 74 publications
0
109
0
Order By: Relevance
“…Several analyses support the conservation and coordination of a posteriorly directed 'wave of buccal expansion' among odontocetes (Summers et al, 1998;Wainwright et al, 2008). The sequence and timing of kinematics appear conserved among odontocetes (Fig.4), with a posteriorly directed wave of expansion from the tips of the jaws through the hyolingual apparatus.…”
Section: Comparative Kinematic Analysesmentioning
confidence: 82%
“…Several analyses support the conservation and coordination of a posteriorly directed 'wave of buccal expansion' among odontocetes (Summers et al, 1998;Wainwright et al, 2008). The sequence and timing of kinematics appear conserved among odontocetes (Fig.4), with a posteriorly directed wave of expansion from the tips of the jaws through the hyolingual apparatus.…”
Section: Comparative Kinematic Analysesmentioning
confidence: 82%
“…To compare levels of variation, it is necessary to use measures that account for the strong correlation between mean duration of the behavior and the standard deviation for the behavior stemming from the fact that cycle duration variance increases with cycle time (Ross et al, 2007a;Wainwright et al, 2008). This was done in two ways.…”
Section: Statistical Designmentioning
confidence: 99%
“…In support of this hypothesis, Ross and colleagues showed that mammalian chew cycle durations not only are less variable than those of lepidosaurs but also increase with mandible length, which does not occur among lepidosaurs. These authors hypothesized that improved chewing rhythmicity, a form of stereotypy (sensu Wainwright et al, 2008), enables mammals to chew for longer, facilitating the acquisition of the greater amounts of food required by their elevated metabolism (Nagy, 2005). Ross and colleagues also suggested that size-related changes in chew cycle durations in mammals support the hypothesis that energy consumption during chewing is minimized by adjusting chew frequency to the natural frequency of the chewing system (Ross et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…However, gait mechanics are not perfectly reproduced between steps, leading to some level of variation even under restricted conditions (Wainwright et al, 2008). In particular, small quadrupedal mammals would be expected to match their high level of structural flexibility [flexed three-segmented limbs with low limb stiffness when running (Farley et al, 1993;Fischer et al, 2002)] with high functional variation during locomotion.…”
Section: Introductionmentioning
confidence: 99%